To Intervene or Not to Intervene: An Experimental Methodology Measuring Actual Bystander Behaviour - Danielle Labhardt; Nadine McKillop; Emma Holdsworth; Sarah Brown; Douglas Howat; Christian Jones (Behavioral Sciences)
Bystander intervention and sexual assault research typically rely on self-reported intent to intervene. However, predicted behaviour can be considerably different from actual behaviour. Hypothetical scenarios are often utilised to remove extenuating circumstances, limiting insight into actual behaviour where those circumstances impact intervention. This paper discusses the development and evaluation of an innovative methodology to measure actual bystander behaviour when witnessing signs of an impending sexual assault. With careful attention paid to ethical considerations and participant safety, 13 participants were directly deceived about the true aim of the research. Utilising observational data and a funnelling debrief, the findings demonstrated varied reactions to sexual assault cues, from not noticing and therefore not intervening, to noticing and (in)directly intervening. Participants’ responses indicated they remained unaware of the deception until it was formally revealed, suggesting the methodology effectively realised the study’s aims. The funnelling debrief mitigated the adverse effects of the deception, with some participants reporting more confidence and motivation to intervene in the future. Further development of this methodology could create more interactive bystander intervention programmes that teach people to identify signs of a sexual assault, develop skills to safely intervene, and raise awareness about sexual violence.